Diseases, peasants, and nation-building in rural China : social conformity, institutional strengthening, and political indoctrination - Fang, Xiaoping (Routledge, 2021)
In 1949, the newly-established communist government claimed that the People’s Republic of China was a socialist country ruled by a people’s democratic dictatorship under the leadership of the working class, based on the union of workers, peasants, and soldiers. This new state system immediately embarked upon a state-building process, a project which included industrialization, collectivization, and conscription. Since China had a predominantly rural population, the peasantry naturally provided the main source of personnel for these movements. This paper examines how the health problems of workers, peasants, and army recruits motivated the state’s efforts to initiate disease eradication and prevention campaigns in rural areas. This paper also addresses how this campaign was implemented by the top-down command structure of the state system and how it contributed to the state-building process in the early years of the socialist era.